2019
DOI: 10.25174/2249-4065/2018/83717
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and association study in some hulled and hulless genotypes of barley (Hordeum vulgare L.)in north western Himalayan region

Abstract: The experimental material comprising of 31 genotypes along with four checks of barley were evaluated in Randomized Block Design with three replications over two years during Rabi, 2016-17 and Rabi, 2017-18. Sufficient genetic variability was observed for all the characters in pooled over environments. High PCV and GCV (>20%) values alongwith high heritability coupled with high genetic advance was recorded for number of grains per spike, biological yield per plant and seed yield per plant which indicated the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…Direct and indirect effects of these components determined on grain yield at genotypic level are presented in Table 2. The results of path coefficient analysis revealed that days to maturity (0.477) exerted the highest positive direct effect on grain yield followed by 1000-grain weight (0.218), spike length (0.060), plant height (0.041) and number of grains per spike (0.040), which support the findings of Devi et al [10] except for number of tillers per meter however, Kumar et al [9] in their findings mentioned positive direct effect of number of tillers per meter on grain yield. Therefore, these traits could be considered as main components for selection in a breeding program for higher grain yield.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Direct and indirect effects of these components determined on grain yield at genotypic level are presented in Table 2. The results of path coefficient analysis revealed that days to maturity (0.477) exerted the highest positive direct effect on grain yield followed by 1000-grain weight (0.218), spike length (0.060), plant height (0.041) and number of grains per spike (0.040), which support the findings of Devi et al [10] except for number of tillers per meter however, Kumar et al [9] in their findings mentioned positive direct effect of number of tillers per meter on grain yield. Therefore, these traits could be considered as main components for selection in a breeding program for higher grain yield.…”
Section: Resultssupporting
confidence: 78%
“…3 20 and number of grains per spike with effective tillers per meter; and number of grains per spike with 1000-grain weight, thereby indicating that these traits could not be improved simultaneously. Some authors also reported significant positive correlation for days to heading with maturity [8], plant height with spike length [9], days to maturity with days to maturity and spike length; plant height with spike length and number of grains per spike [10]. The negative and significant relation of effective tillers per meter with plant height and number of grains per spike; 1000-grain weight with number of grains per spike also corroborated with the findings of Devi et al [10] under different environments.…”
Section: Resultsmentioning
confidence: 99%
“…Recent exploration regarding salutary composition in food barley has renewed the interest attesting the health benefits of barley in daily diets (Brockman et al, 2013; Sullivan et al, 2013). Due to its ample environmental and morphological rigidity, colourful types of barley (downtime, spring, two-rowed, six-rowed, awned, awnless, hooded, covered, naked, malting, feed and food types) are grown throughout the world (Kumar et al, 2018). The most essential pre-requisite for planning and prosecution of a resourceful parentage programme is the vacuity of desirable inheritable variability for important characters in the genotypes (Sunil et al, 2017).…”
Section: Introductionmentioning
confidence: 99%